An Assessment of the Niger Delta Amnesty Programme in Southern Ijaw Local Government Area of Bayelsa State, Nigeria - ADEDEJI, Oluwatosin Bethel (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2023)
The Niger Delta region of Nigeria generates 95% of export earnings and about 40% of the Nigerian government revenue (IMF). This region was known for its calmness and peacefulness until the discovery of oil in the Oloibiri community, Ogbia Local Government Area of present-day Bayelsa State in 1956. The discovery and exploration of oil in the Niger Delta region gave birth to the destruction of the environment, livelihood and agitation for resource control and the development of the region. The continued neglect of the environment by the government and the oil companies coupled with the rise in unemployment and youth restiveness gave birth to militant groups that killed, kidnapped and vandalised oil installations. The Nigerian government in response to the plight of the Niger Delta people introduced the amnesty programme in 2009. This research work, therefore, assesses the Niger Delta amnesty programme in the Southern Ijaw Local Government Area of Bayelsa State. It further assesses the extent to which the amnesty programme has addressed the root causes of the Niger Delta crisis. The study adopted a descriptive research design (qualitative method), using both primary and secondary data collection. The theory of change and utilization-focused evaluation is used for the study. The findings of this research established that the amnesty programme has not fully addressed the root causes of the Niger Delta conflict. Given this, for the amnesty programme to be effective, the government should make provisions for employment and social amenities in the Niger Delta region.